Celebrity Endorser and Brand Image McDonald’s: Impact of Collaboration McDonald's with BTS in Indonesia - Saragih, Melva Hermayanty Saragih; Sulaiman, Varian Kashira; Shani, Haikal; Holando, Steven (Business Economic, Communication, and Social Sciences Journal (BECOSS), 2024)
Celebrity Endorsement is one of the marketing strategies businesses often use to increase purchasing power. Famous artists are also paid handsomely to endorse business products. This research aims to determine the extent of BTS’s influence as a Celebrity Endorser of the fast-food McDonald’s BTS Meal Collaboration in Jakarta. Apart from that, researchers also examined the influence of Mc Donalds’ own brand image on fast food purchase intention. This quantitative research took a sample of 100 respondents who were McDonald’s customers. The research results show that the Celebrity Endorser and Brand Image variables do have a significant influence on the purchase intention of the fast-food brand.